2006
DOI: 10.1530/eje.1.02056
|View full text |Cite
|
Sign up to set email alerts
|

Three-month sustained-release triptorelin (11.25 mg) in the treatment of central precocious puberty

Abstract: Objective: Depot GnRH agonists are commonly used in the treatment of central precocious puberty (CPP). The triptorelin 11.25 mg 3-month depot, currently used in adult indications, had not previously been evaluated in CPP. Design: This was a multicenter, open-label, 12 month trial conducted in 64 CPP children (54 girls and 10 boys), treated quarterly. Methods: Children with a clinical onset of pubertal development before the age of 8 years (girls) or 9 years (boys), pubertal response of LH to GnRH $ 7 IU/l, adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 23 publications
9
59
0
6
Order By: Relevance
“…Correct diagnosis of the etiology of sexual precocity is critical, because treatment of patients with PPP is different from those with CPP, and some PPP can secondarily evolve into CPP (6). Standard treatment of CPP is to suppress the activation of HPGA (7) through periodically using GnRH agonists such as leuprorelin depot (8) and triptorelin depot (9,10). Patients with CPP have to continue receiving this medication until they reach the average age of the onset of puberty.…”
mentioning
confidence: 99%
“…Correct diagnosis of the etiology of sexual precocity is critical, because treatment of patients with PPP is different from those with CPP, and some PPP can secondarily evolve into CPP (6). Standard treatment of CPP is to suppress the activation of HPGA (7) through periodically using GnRH agonists such as leuprorelin depot (8) and triptorelin depot (9,10). Patients with CPP have to continue receiving this medication until they reach the average age of the onset of puberty.…”
mentioning
confidence: 99%
“…With triptorelin 11.25 mg 3-month depot, Carel et al [4] found GnRH-stimulated peak LH was suppressed (≤3 IU/l) in 85% of the children at 3 months, 97% at 6 months and 95% at 12 months of treatment, and pubertal development regressed in most patients. In children given different doses of leuprolide sequentially (7.5 mg every 4 weeks for a minimum of 24 weeks, 3.75 mg every 4 weeks for 12 weeks and 11.25 mg with assessment after 3 months), Badaru et al [2] noted higher LH and FSH levels with both 3.75 mg and 11.25 mg at 3 months compared with 7.5 mg.…”
Section: Discussionmentioning
confidence: 99%
“…While such longer-acting preparations potentially provide greater convenience for the child and family, as yet there are limited data on their efficacy compared to the one-month formulation [2,3,4,5,6]. Suppression of gonadotrophin levels in children with CPP has been found to be comparable for the one- and three-month preparations of leuprorelin [2, 3] and triptorelin [4] given for 3–12 months. Other investigators have reported the results of longer duration of treatment with goserelin [5, 6].…”
Section: Introductionmentioning
confidence: 99%
“…Estudos recentes revelaram a mesma eficácia e segurança dos a-GnRH de uso mensal, trimestral e anual (8,28,(35)(36)(37). O regime terapêutico da PPC com análogos de aplicação trimestral, aprovado no Brasil, permite a redução do número das aplicações anuais, favorecendo a adesão ao tratamento da PPC (8,38).…”
Section: Tratamento Da Puberdade Precoce Centralunclassified